La Ricerca-Formazione (FrancoAngeli, 2025)
This volume presents the work of a research group based at the Centre for Educational Research on Teacher Professional Development (CRESPI) in Italy. The research objective was to produce a model for defining indicators of impact for evaluating research-based professional learning projects, developing tools and procedures for gathering relevant data, and identifying factors that can facilitate and impede the progress of the projects.